Association of the triglyceride glucose index with all cause and CVD mortality in the adults with diabetes aged < 65 years without cardiovascular disease - Chang Liu; Dan Liang; Guoan Xiang; Xuanbo Zhao; Kun Xiao; Lixin Xie (Scientific Reports)
Abstract Although the triglyceride-glucose (TyG) index has been established as a valuable predictor for cardiovascular disease (CVD) and cardiovascular mortality, there is limited research exploring its association with all-cause or CVD mortality specifically in adults with diabetes aged < 65 years without cardiovascular disease. This study aimed to investigate the relationship between the TyG index and both all-cause and CVD mortality in this population within the United States. Our study recruited 1778 adults with diabetes aged < 65 years without cardiovascular disease from the National Health and Nutrition Examination Survey (NHANES) 2003–2018. Mortality outcomes were determined by linking to National Death Index (NDI) records up to December 31, 2019. Cox regression modeling was employed to examine the association between the TyG index and mortality in this population. The nonlinear relationship between the TyG index and mortality was assessed using restricted cubic splines (RCS). Additionally, subgroup analyses and interaction tests were conducted to explore potential effect modifiers. A total of 1788 participants were included in the final cohort, with an average age of 49.61 ± 0.32 years. During a median follow-up of 7.92 years, the occurrence of 150 all-cause deaths and 33 CVD-related deaths were recorded. To investigate the independent association between the TyG index and the risks of all-cause and CVD mortality, three Cox regression models were developed. In Model 1, a significant positive association was observed between the TyG index and the risk of all-cause mortality (HR 1.38, 95% CI 1.09–1.74). This association persisted in the minimally adjusted model (HR 1.44, 95% CI 1.13–1.83), which was adjusted for age, gender and race. Even after full adjustment, this positive association remained significant (HR 1.91, 95% CI 1.36–2.70). We also found that the relationship between the TyG index and all-cause mortality was linear. Subgroup analyses revealed no significant interactions between the TyG index and the stratification variables. However, we did not observe a significant association between the TyG index and CVD mortality in this population. Our results suggested that a significantly positive association between the TyG index and all-cause mortality. The positive association between the TyG index and all-cause mortality was linear. We did not observe a significant association between the TyG index and CVD mortality.